The effects of surface roughness on the fully developed heat transfer characteristics of laminar and transitional flow through horizontal circular tubes - Everts, Marilize (University of Pretoria, 2022)
Dissertation (MEng (Mechanical Engineering)--University of Pretoria, 2022.